The Effect of Human Resource Competency and Internal Control System on Financial Statement Quality with Accounting Information System as a Moderating Variable - I Kadek Agus Sumayasa; I Gusti Lanang Putu Tantra; Ni Made Rai Juniariani; I Wayan Kartana; A.A Bagus Amlayasa (International Journal of Entrepreneurship and Business Management, 2026)
Financial records are crucial for LPD because they demonstrate management's responsibility to the traditional village community, aid decision-making, and ensure transparent fund management. This study examines internal control mechanisms, human resource competence, and financial report quality in Gianyar Regency LPDs. The study sampled 103 of 270 participants. Purposive sampling was used. The survey included 103 Gianyar Regency LPD chairpersons. This study uses SmartPLS for SEM research. The study found that human resource competency, internal control systems, accounting information systems, and the effects of the internal control system on financial statements are all positive and significant.